2012
DOI: 10.1111/j.1525-1446.2012.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Effects Related to Pesticide Use on Athletic Fields

Abstract: The use of pesticides on athletic fields presents many possible health hazards. Results indicate that there is a significant risk of exposure to pesticide for children engaged in sports activities. Given that children are also often concurrently exposed to pesticides as food residues and from home pest management, we need to examine opportunities to reduce their exposures. Both policy and practice questions are raised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It is known that households with children commonly use and store pesticide products. [1][2][3] The use of pesticides at child care facilities, 4 on athletic fields, 5 and on school grounds 6 could all present potential exposures and health hazards to children. Because children's immune systems are still developing, they may provide less protection than adult immune systems.…”
mentioning
confidence: 99%
“…It is known that households with children commonly use and store pesticide products. [1][2][3] The use of pesticides at child care facilities, 4 on athletic fields, 5 and on school grounds 6 could all present potential exposures and health hazards to children. Because children's immune systems are still developing, they may provide less protection than adult immune systems.…”
mentioning
confidence: 99%
“…Pesticides that schools use in treating and maintaining school grounds have also been found to pose health risks to children (Alarcon et al, 2005;Gilden et al, 2012). or after treatment (Chatham-Stephens et al, 2011, and can also be tracked inside the building by students and faculty (Nishioka et al, 2001).…”
Section: Environmental Hazards In Schoolsmentioning
confidence: 99%
“…Furthermore, the use of pesticides for the maintenance of school grounds has become a mounting point of concern because of the potential health impacts on citizens, particularly children, who may be exposed to the pesticides (Alarcon et al, 2005;Gilden et al, 2012). Currently, there is no evidence linking childhood cancer to pesticide exposure on school grounds or athletic fields (Chen et al, 2015;Gilden et al, 2012;Morgan et al, 2005;Niehoff et al, 2016). Notably, Chen et al (2015) found no association between outdoor pesticide exposure and cancer, but increased cancer incidence with increased indoor pesticide exposure.…”
mentioning
confidence: 99%